Progesterone regulates the expression and activity of two mouse isoforms of the glycoprotein folding sensor UDP-Glc: Glycoprotein glucosyltransferase (UGGT) - Prados, Maria Belen (2013)
UDP-Glucose:glycoprotein glucosyltransferase (UGGT) is a central component of the endoplasmic reticulum (ER) glycoprotein-folding quality control system, which prevents the exit of partially folded species. UGGT activity can be regulated by the accumulation of misfolded proteins in the ER, a stimulus that triggers a complex signaling pathway known as unfolded protein response (UPR) which is closely associated with inflammation and disease. In this work, we investigated the effect of progesterone (P4) on the expression and activity of UGGT in a mouse hybridoma. We detected the expression of two UGGT isoforms, UGGT1 and UGGT2, and demonstrated that both isoforms are active in these cells. Interestingly, the expression of each isoform is regulated by high physiological P4 concentrations. This work provides the first evidence of a hormonal regulation of UGGT isoform expression and activity, which might influence the glycoprotein quality control mechanism. These findings could contribute to the study of pathologies triggered by the accumulation of misfolded proteins.